The Effect of Scaffolding Provision an Acid and Base Learning Project on Students' Science Process Skills - Tri Haryati; Muhammad Rusdi; Rayandra Asyhar; Muhammad Haris Effendi Hasibuan; Rahadian Zainul (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this study was to investigate the effect of the scaffolding guidance provision on students' science process skills (SPS) in a project-based learning (PjBL) about acid and base concepts. A quasi-experimental research design was applied to collect data using a pre-validated SPS-observation. An experiment group of students of SMAN 3 in Jambi City had learnt the concepts using a scaffolding-assisted PjBL while a control group from the same school had learnt it using PjBL without scaffolding. Data was analyzed using t-test assisted by SPSS software. The results of analyses showed that the SPS of the experiment group was higher than their counterparts’ SPS. Statistical analyses showed an effect of the use of the scaffolding guidance on the students’ SPS with the p-value of .000 < .05. The experiment students had been observed achieved the indicators of the SPS during the learning process while their counterparts had not; and those may be due to the benefits of the provision of the scaffolding guidance that eased them to do their tasks. It can be concluded that the use of scaffolding guidance is able to overcome the problems faced by students in a project-based learning that thus improve their SPS